Coexistence of Two Rare Genetic Variants in Canonical and Non-canonical Exons of SCN5A: A Potential Source of Misinterpretation - Shestak, Anna G.; Makarov, Leonid M.; Komoliatova, Vera N.; Kolesnikova, Irina V.; Skorodumova, Liubov O.; Generozov, Edward V.; Zaklyazminskaya, Elena V. (Frontiers in Genetics, 2021)
Primary cardiac channelopathies are a group of diseases wherein the role of DNA testing in aiding diagnosis and treatment-based decision-making is gaining increasing attention. However in some cases, evaluating the pathogenicity of new variants is still challenging. We report an accurate multistage assessment of a rare genetic variant in the SCN5A gene using NGS techniques and Sanger sequencing. Female sportsman (14 y.o.) underwent genetic counseling and DNA testing due to QT interval prolongation registered during ECG Holter monitoring. Genetic testing of the proband was performed in two independent laboratories. Primary DNA testing was performed by ES using the Ion Proton™ System. Target panel sequencing of 11 genes was performed using PGM IonTorrent. Search for variants in noncanonical and canonical exons 6 was performed by Sanger sequencing. The cascade familial screening and control re-sequencing were provided for proband with identified genetic variant p.S216L (g.38655290G>A, NM_198056.2:c.647C>T, rs41276525) in the canonical exon 6 of the SCN5A gene after receiving data from another laboratory. Control Sanger and NGS sequencing revealed the absence p.S216L in the canonical exon 6 and confirmed the presence of p.S216L (g.38655522G>A, c.647C>T, rs201002736) in the noncanonical exon 6 of the SCN5A gene. The identified variant was re-interpreted. The noncanonical transcripts of the exon 6 of the SCN5A gene is poorly represented in cardiac tissue (gnomAD). The detected variant was found in proband’s healthy mother. The correct interpretation of genetic data requires close cooperation between cliniciants and researchers. It can help to avoid financial costs and stress for probands and families.